With the margins: Writing subaltern resistance and social transformation. Issue 2 (25th November 2020) - Vijay, Devi; Gupta, Shalini; Kaushiva, Pavni
Abstract: In this study, we surface the problems of representation mainstream organizational theory encounters in documenting and telling accounts of subaltern actors and social transformation. We explore how writing practices that draw on feminist postcolonial literary traditions can transform organizational studies of social change. Drawing on three literary texts—Mahasweta Devi's Draupadi, Urmila Pawar's The Weave of My Life, and Arundhati Roy's Ministry of Utmost Happiness —we reflect on how we may represent the lives of others. Inspired by these three writers, we suggest solidaristic transgression, unsettled habitation, and counter‐discursive memory work as three modes of engagement that challenge us as academics writing for change.